2010
DOI: 10.4103/0976-500x.64531
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of glibenclamide against nicotinamidestreptozotocin induced nuclear damage in diabetic Wistar rats

Abstract: Objective:To evaluate the protective effect of glibenclamide against the experimental diabetes-induced nuclear damage in Wistar rats.Materials and Methods:The anti-mutagenic effect of glibenclamide (0.5, 5 and 50 mg/kg, p.o daily for 4 weeks) was evaluated against the nicotinamide (NA)-streptozotocin (STZ) induced type-2 diabetes mellitus using bone marrow micronucleus and sperm abnormalities tests. The antioxidant status was tested by estimating the serum levels of lipid peroxidation (LPO), catalase (CAT), su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…Dose of STZ in the second round of injection was reduced to 50 mg/kg. Administration of nicotinamide before the streptozotocin injection to the mice protects β-cells from STZ-induced severe cytotoxic damages, leading to chronic DM by producing moderate hyperglycemia4243. In the present study, the plasma insulin levels in diabetic mice were much higher than those in normal mice, but did not disappear completely (Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 41%
“…Dose of STZ in the second round of injection was reduced to 50 mg/kg. Administration of nicotinamide before the streptozotocin injection to the mice protects β-cells from STZ-induced severe cytotoxic damages, leading to chronic DM by producing moderate hyperglycemia4243. In the present study, the plasma insulin levels in diabetic mice were much higher than those in normal mice, but did not disappear completely (Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 41%
“…Upon induction of a diabetic state through administration of nicotinamidestreptozotocin, the overall fertility parameters were affected showing an increase in shape abnormality and a reduction in sperm count as well as testis weight. However, after treatment with glibenclamide, there was a decrease in shape abnormality, although no changes in sperm count were observed (Rabbani et al 2010b). Similarly, the SU glimepiride was observed to have the same protective effect (Rabbani et al 2009).…”
Section: Sulphonylureas and Meglitinidesmentioning
confidence: 89%
“…This study has shown their spermicidal potential in vitro by describing a total loss of human sperm viability and motility, possibly due to an elevation of intrasperm calcium concentration ([Ca 2+ ]is), that the authors proved to be resulting from the inhibition of the K ATP channels (Kumar et al 2008). In a different study, it was proved that glibenclamide exerted protective effects on diabetic rats' fertility (Rabbani et al 2010b). Upon induction of a diabetic state through administration of nicotinamidestreptozotocin, the overall fertility parameters were affected showing an increase in shape abnormality and a reduction in sperm count as well as testis weight.…”
Section: Sulphonylureas and Meglitinidesmentioning
confidence: 99%
See 2 more Smart Citations